Energy requirements and allowances of exercising horse - Martin-Rosset, William (MTT, 2008)
In this review, requirements proposed by several countries using different systems (NRC- 2007, GEH-1994, INRA-1990, CVB-2006, SCAN-2004) are described and discussed. Energy requirements are evaluated using either factorial method (GEH-1994 and CVB-2006) and a model which predicts oxygen consumption or feeding trial method (INRA-1990) based on nutritional balance which include the variation of body weight and body condition score whereas the intensity of work is stated both on oxygen consumption and practical observations. NRC-2007 and SCAN-2004 proposed to assign the increments of exercise requirement as multiple of maintenance requirement based more or less on factorial method. The increments of the requirements with the intensity of exercise in respect of maintenance (base =100) are more or less consistent between the different systems, in spite the intensity of exercise does not means the same work and the model used to predict oxygen consumption are different. Additional requirements to young horses (yearlings and long yearlings) during the training period are requested and suggested by all the systems to support the increase of the muscle mass due to simultaneous late growth and exercise. Recommended allowances including requirements for different body weight and exercise intensity are provided by all the systems but the range of intake capacity - diet composition and key body condition score along the training and competition period are not always suggested.
Keywords: Ko; horse; exercise; energy; requirements